Hygiene Sanitation of Drinking Water Depots in the Work Area of the Rejosari Health Center in 2022: Hygiene Sanitasi Depot Air Minum Di Wilayah Kerja Puskesmas Rejosari Tahun 2022 - Mutiara Arnanda; M. Kamali Zaman; Herlina Susmaneli (Jurnal Olahraga dan Kesehatan (ORKES), 2022)
Drinking Water Depot Sanitation Hygiene is a health effort that reduces or eliminates factors that cause pollution to drinking water, handlers, and equipment used that may cause health problems. Based on data from the Pekanbaru City Health Service in 2020, the number of water depots in Pekanbaru City is 666 depots. In the District of Tenayan Raya there are 35 water depots under the auspices of the Rejosari Health Center spread over 6 villages. The purpose of this study is to analyze the sanitation hygiene of drinking water depots in the working area of the Rejosari Health Center in 2022. This type of research is qualitative with a qualitative descriptive. This research was conducted in July 2022 in the Rejosari Health Center Work Area, Pekanbaru City. Collected data using in-depth interviews and observations to 10 informants consisting of 1 healthty officer, 3 owners, 3 workers, 3 consumers. The results of this study indicate that the water depot in the working area of ​​the Rejosari Health Center does not meet the hygiene and sanitation requirements, because the depot is made very simple which should have its own laundry room, its own filling room and space for its own transportation. Equipment such as gallon cleaning brushes have fallen out, the ceiling and paint of the depot have faded due to water seepage, the handlers have never checked their health at the health facilities, this causes it to be unknown whether the handlers have infectious diseases. It is hoped that the Puskesmas will provide guidance to the depot if the sanitation conditions of the place, production equipment, and employee hygiene are not in good condition.